2013
DOI: 10.1159/000351945
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Cardiovascular Disease

Abstract: This chapter examines the association of anxiety disorders and anxiety symptoms with cardiovascular disease, focussing on hypertension (an independent risk factor for myocardial infarction and stroke) and coronary heart disease. In both cases, epidemiological data linking the cardiovascular disorder with specific anxiety disorders and anxiety symptoms are examined first, and evidence relating to putative mechanisms that may underlie these associations is explored. For hypertension, an association with panic at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 75 publications
(80 reference statements)
1
8
1
Order By: Relevance
“…A recent meta‐analysis indicated that women with PCOS tend to experience mildly elevated levels of anxiety and depression, significantly more than women without PCOS . Anxiety and depression are linked to sympathetic dysfunction, in particular with an abnormal sympathetic nerve firing pattern, and elevated cardiovascular risk . In the present study, however, state and trait anxiety did not differ between the two groups of women.…”
Section: Discussionsupporting
confidence: 92%
“…A recent meta‐analysis indicated that women with PCOS tend to experience mildly elevated levels of anxiety and depression, significantly more than women without PCOS . Anxiety and depression are linked to sympathetic dysfunction, in particular with an abnormal sympathetic nerve firing pattern, and elevated cardiovascular risk . In the present study, however, state and trait anxiety did not differ between the two groups of women.…”
Section: Discussionsupporting
confidence: 92%
“…While the relationship between severe mental illness and cardiovascular disease has been widely explored, there is a paucity of evidence around the relationship between anxiety and incident cardiovascular events. (Bowen et al, 2000;Davies and Allgulander, 2013;Lambiase et al, 2014;Osborn et al, 2007) The burden of CVD and CVD risk factors is increasing rapidly amongst young, working-age adults. (Lavie and Milani, 2006;Moran et al, 2014;Poisson et al, 2014) Since cardiovascular disease is the leading cause of loss of in disability adjusted lifeyears (DALYs) worldwide, this represents the greatest loss for families and national economies.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with high levels of chronic stress, anxiety, and sleep problems also show many of the same CHD-relevant biological patterns noted above, including cardiac autonomic dysfunction, impaired endothelial functioning, low-grade inflammation, and platelet hyperactivity (Davies & Allgulander, 2013; Edmondson & Cohen, 2013; Everson-Rose & Lewis, 2005; Motivala, 2011; Steptoe & Kivimaki, 2012). However, much of the evidence regarding these associations derives from studies of otherwise healthy individuals.…”
Section: Mechanisms Linking Psychological Comorbidities To Coronary Hmentioning
confidence: 80%